The resilient founder : lessons in endurance from startup entrepreneurs - Ramsinghani, Mahendra (Ascent Audio, 2022)
In The Resilient Founder, Mahendra Ramsinghani gathers insights from over a hundred founders to deliver an intuitive and insightful guide to understanding our psychology and navigating the psychological pressures of startup leadership. Venture backed companies are expected to grow at high velocity, raise large amounts of capital, and build teams effectively to achieve unicorn, no decacorn status. Yet the journey is long, filled with uncertainties, extremities, and black swan events. It can wear out the best and the brightest. The role of a founder can be lonely, frustrating, and filled with high-highs and low-lows-all of this leading to anxiety, depression, and even suicide. The Resilient Founder addresses the fundamentals of understanding our own inner workings and explores practical ways of overcoming our inner hurdles. Filled with simple, yet concrete strategies, lessons and insights, founders and business leaders can work with stress, anxiety, and other mental challenges presented by the life of an entrepreneur. In this book, listeners will learn to: understand the basics of founder psychology, and how our inner workings can help or hurt us; the importance of building a healthy ego, leading to resilience; and draw on the lessons of established startup leaders on how to wrestle with their own mental and emotional challenges.